2008
DOI: 10.1016/j.jsb.2007.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Structures of open (R) and close (T) states of prephenate dehydratase (PDT)—Implication of allosteric regulation by l-phenylalanine

Abstract: The enzyme prephenate dehydratase (PDT) converts prephenate to phenylpyruvate in Lphenylalanine biosynthesis. PDT is allosterically regulated by L-Phe and other amino acids. We report the first crystal structures of PDT from Staphylococcus aureus in a relaxed (R) state and PDT from Chlorobium tepidum in a tense (T) state. The two enzymes show low sequence identity (27.3%) but the same prototypic architecture and domain organization. Both enzymes are tetramers (dimer of dimers) in crystal and solution while a P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
39
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 56 publications
7
39
0
Order By: Relevance
“…Since E. coli crude extract contains endogenous PDT activity derived from a bifunctional CM-PDT enzyme (Davidson et al, 1972;Zhang et al, 1998), CM activity was analyzed in the purified fraction to ensure the absence of E. coli CM-PDT contamination. Consistent with the prior report (Tan et al, 2008), PDT activity was detectable only at high enzyme concentrations and prolonged reaction times (Supplemental Figure 5). When incubated with arogenate substrate, however, the C. tepidum ADT homolog was able to produce Phe efficiently (Supplemental Figure 5).…”
Section: Tepidum Adt Homolog Converts Arogenate Into Phesupporting
confidence: 91%
See 2 more Smart Citations
“…Since E. coli crude extract contains endogenous PDT activity derived from a bifunctional CM-PDT enzyme (Davidson et al, 1972;Zhang et al, 1998), CM activity was analyzed in the purified fraction to ensure the absence of E. coli CM-PDT contamination. Consistent with the prior report (Tan et al, 2008), PDT activity was detectable only at high enzyme concentrations and prolonged reaction times (Supplemental Figure 5). When incubated with arogenate substrate, however, the C. tepidum ADT homolog was able to produce Phe efficiently (Supplemental Figure 5).…”
Section: Tepidum Adt Homolog Converts Arogenate Into Phesupporting
confidence: 91%
“…The weak to no PPA-AT activity detected in the Synechocystis AspAT Ib enzyme (Table 1; Graindorge et al, 2014) is consistent with the presence of BCAT-type enzymes having strong PPA-AT activity with broad substrate specificity in cyanobacteria (Stenmark et al, 1974;Jensen and Stenmark, 1975;Graindorge et al, 2014). Also, the ADT homolog of C. tepidum, previously reported as PDT (Tan et al, 2008), showed 10-fold higher catalytic efficiency for ADT than PDT activity (Table 2), whereas cyanobacteria such as Synechocystis process a bifunctional CM-PDT enzyme (Kaneko et al, 1996) and lack ADT activity (Stenmark et al, 1974;Hall et al, 1982). These phylogenetic and biochemical results together suggest that both PPA-AT and ADT, and thus the arogenate Phe pathway, were acquired by a eukaryotic ancestor of plants from a bacterial lineage that gave rise to sister phyla Chlorobi and Bacteroidetes.…”
Section: Evolutionary History Of Plant Phe Biosynthesissupporting
confidence: 77%
See 1 more Smart Citation
“…Several crystal structures of ACT domains that bind small ligands have been reported. The binding site for PheH is most similar to that of bacterial prephenate dehydratase (35); only three of the six residues identified here are conserved in that protein.…”
Section: Discussionmentioning
confidence: 84%
“…Helical content calculated from the primary sequences of these archaeal TyrAs using secondary structure prediction programs was between 50 and 60 %. These values are typical for many CM, PD, and PDT proteins from other organisms, including hyperthermophiles (Chiu et al 2010;Kleeb et al 2006;Lee et al 1995;Sun et al 2006;Tan et al 2008). The unfolding of IhTyrA and NeTyrA by thermal denaturation was followed by measuring changes in ellipticity at 222 nm (Fig.…”
Section: Figmentioning
confidence: 97%